Born at midnight - Hunter, C. C. (St. Martin's Press, 2011)
Sixteen-year-old Kylie Galen thinks her misbehavior in the wake of her grandmother's death and her parents' separation are the reasons she has been sent to Shadow Falls Camp, but learns it is a training ground for vampires, werewolves, and other "freaky freaks," of which she may be one.